JOINT PROPERTY OWNERSHIP OF SPOUSES ACCORDING TO SHARIAH TRADITIONS AND PRINCIPLES IN MALAY REGION - Nurafni; Aslati; Darmawan Tia Indrajaya (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the interaction between the concept of shared property in Malay custom and the principle of "dhimmah maliyah" in sharia, aiming to analyze differences and similarities in the practice of joint property ownership. With the framework of legal pluralism and a socio-legal qualitative approach, the study found the formation of a hybrid system. The fundamental difference lies in the communal principle of customary versus individual sharia. The similarities are found in syncretic practices where customary principles dominate acquired property during marriage, while sharia principles are applied selectively to inherited property and inheritance, suggesting the existence of creative negotiations.